Jasmonate and Melatonin Act Synergistically to Potentiate Cold Tolerance in Tomato Plants - Ding, Fei; Ren, Liming; Xie, Fang; Wang, Meiling; Zhang, Shuoxin (Frontiers in Plant Science, 2022)
Both jasmonic acid (JA) and melatonin (MT) have been demonstrated to play positive roles in cold tolerance, however, whether and how they crosstalk in the cold responses in plants remain elusive. Here, we report that JA and MT act synergistically in the cold tolerance in tomato plants (Solanum lycopersicum). It was found that JA and MT were both substantially accumulated in response to cold stress and foliar applications of MeJA and MT promoted cold tolerance as evidenced by increased Fv/Fm, decreased relative electrolyte leakage (EL) and declined H2O2 accumulation in tomato plants. Inhibition of MT biosynthesis attenuated MeJA-induced cold tolerance, while inhibition of JA biosynthesis reduced MT accumulation in tomato plants under cold conditions. Furthermore, qRT-PCR analysis showed that the expressions of two MT biosynthetic genes, SlSNAT and SlAMST, were strongly induced by MeJA, whereas suppression of SlMYC2, a master JA signaling regulator, abated the expressions of SlSNAT and SlAMST under cold stress. Additionally, suppression of SlMYC2 reduced MT accumulation, decreased Fv/Fm and increased EL in cold-stressed tomato plants. Interestingly, exogenous MT promoted JA accumulation, while inhibition of MT biosynthesis significantly reduced JA accumulation in tomato plants under the cold condition. Taken together, these results suggest that JA and MT act cooperatively in cold tolerance and form a positive feedback loop, amplifying the cold responses of tomato plants. Our findings might be translated into the development of cold-resistant tomato cultivars by genetically manipulating JA and MT pathways.